2006
DOI: 10.1159/000091217
|View full text |Cite
|
Sign up to set email alerts
|

External and Extreme Capsular Stroke: Clinical, Topographical and Etiological Patterns

Abstract: Background and Purpose: To characterize clinically acute external (EcC) and extreme capsular (ExC) strokes in 9 patients with first-ever acute stroke. Methods: Nine patients with a lesion limited to the EcC-ExC region proven by diffusion-weighted imaging included in our registry, corresponding to 0.3% of 3,600 patients with ischemic stroke, were studied. Results: We found three main groups of clinical manifestations: (1) motor deficits in all patients (4 with faciobrachial, 2 with faciobrachiocrural, and 1 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…These deficits are in line with known functions of the insula, based on previous electrophysiological, functional and lesional studies [1,20]. For example, Penfield and others [21,22,23,24] have consistently reported somatosensory-but also language-, speech-, vestibular- and motor-evoked responses during stimulation of the insular cortex.…”
Section: Discussionsupporting
confidence: 79%
“…These deficits are in line with known functions of the insula, based on previous electrophysiological, functional and lesional studies [1,20]. For example, Penfield and others [21,22,23,24] have consistently reported somatosensory-but also language-, speech-, vestibular- and motor-evoked responses during stimulation of the insular cortex.…”
Section: Discussionsupporting
confidence: 79%
“…In patients with CMTX, Lee et al (2017) found additional abnormalities (indicated by decreased fractional anisotropy and/or increased radial diffusivity) in several white matter tracts, including the external capsule, the cingulate, the fornix, and the superior longitudinal fasciculus (SLF I). The external capsule is known to consist of fibers mainly supporting cortico-subcortical connections (Kumral & Çalli, 2006;Ribas, Yağmurlu, de Oliveira, Ribas, & Rhoton, 2018). Most importantly, it is often indistinguishable from the extreme capsule in studies utilizing standard neuroradiological evaluation (e.g.…”
Section: Introductionmentioning
confidence: 99%